Metabolism of ochratoxin B and its possible effects upon the metabolism and toxicity of ochratoxin A in rats. - Størmer, F C (1985)
A metabolic product was formed from ochratoxin B by rat liver microsomal fractions in the presence of NADPH. It was isolated from the incubation mixture by extraction, thin-layer chromatography, high-pressure liquid chromatography, and crystallization. On the basis of mass and nuclear magnetic resonance spectroscopy, the structure is suggested to be 4-hydroxyochratoxin B. The Km for the formation of 4-hydroxyochratoxin B was determined, and the hydroxylation of ochratoxin A was not altered by the presence of ochratoxin B. Rats were given ochratoxin A or B, or a mixture of both intraperitoneally. The ratios of the three metabolites, ochratoxin A, (4R)-4-hydroxyochratoxin A, and ochratoxin alpha, excreted in the urine did not change in the presence of ochratoxin B. Ochratoxin B was metabolized to 4-hydroxyochratoxin B and ochratoxin beta, but in a different ratio than for the ochratoxin A metabolites. When given intraperitoneally, ochratoxin beta was excreted within 24 h. In rats treated with ochratoxin A alone, the food intake was reduced by 50%, and histologically severe lesions, degeneration, and necrosis were observed in the proximal tubules. When ochratoxin A and B given in combination, the animals were clinically unaffected and histologically there was only slight damage of proximal tubules. These observations indicate that ochratoxin B considerably reduces the toxic effects of ochratoxin A.